PROBLEMS OF PERSONAL DATA PROTECTION WHEN USING BIG DATA TECHNOLOGIES - Bogdan , Varvara Vladimirovna; Kirillova, Elena Anatolyevna (Journal of Applied Engineering Science, 2020)
The study analyzes Big Data technologies and considers the role, features and significance of these technologies. The relevance of the research is important because of the large-scale use of Big Data technologies in many areas and the weak legal regulation of the employment of Big Data when using personal data. The purpose of this study is to determine the legal status of Big Data technology, differentiate the concepts of "personal data" and "Big Data technology" and offer practical recommendations on the use of this technology. The methodological basis of the research is legal, statistical, private scientific methods, as well as the methods of case analysis and "snowball". Based on the results of the study, the authors define the "Big Data" technology and "personal data in electronic form". The principles for using Big Data technologies that can be applied in the international legal acts and judicial practice were developed. They are: the legality of collecting personal data in electronic form; electronic data processing in limited ways; prohibition of combining various databases with personal information in electronic form; limited period of storage of personal data in electronic form; free use of information; commercial usage. It is proposed to classify personal information provided electronically on the Internet by citizens into the following categories: personal information open to public; special information on actions; biometric data; confidential personal information.
Keywords: Big Data technologies, information, personal data, electronic form, privacy